2019
DOI: 10.1177/0883073818823359
|View full text |Cite
|
Sign up to set email alerts
|

GABA Transaminase Deficiency With Survival Into Adulthood

Abstract: GABA-transaminase deficiency is an ultra-rare disorder of GABA metabolism that was described for decades as an early onset epileptic encephalopathy plus movement disorder and hypersomnolence with mortality in early childhood. We report two affected siblings in adolescence and adulthood, both with profound developmental impairment, intractable epilepsy, movement disorder, and behavioral fluctuations. This considerably expands the phenotype and longevity of this inherited neurotransmitter disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…The variant is pathogenic, resulting in the ABAT deficiency phenotype observed in our case. In comparison to the previous reports, 3,4,8,10,[12][13][14][15][16][17][18] our patient had a previously unreported homozygous missense mutation in the ABAT gene.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The variant is pathogenic, resulting in the ABAT deficiency phenotype observed in our case. In comparison to the previous reports, 3,4,8,10,[12][13][14][15][16][17][18] our patient had a previously unreported homozygous missense mutation in the ABAT gene.…”
Section: Discussioncontrasting
confidence: 76%
“…To date, only 14 patients worldwide have been reported in the published literature with GABA-T deficiency. 3 4 8 10 12 13 14 15 16 17 18 Six of these patients survived for more than 3 years, compared with the previously reported mortality rate within the first 2 years of life. 8 Our patient died at 30 months, which is consistent with previous data.…”
Section: Discussionmentioning
confidence: 72%
“…In conclusion, there is no doubt that the GABA shunt is imperative for health, and its impairment triggers the development of several disease phenotypes, most of which are related to neurological disturbances [13,14,[76][77][78][79]. In this study, we showed that the GABA shunt is a promising route involved in the mitochondrial redox metabolism of cortical and hypothalamic synaptosomes and is linked to glucose metabolism by increasing HK activity at the mitochondrial level.…”
Section: Discussionmentioning
confidence: 62%
“…Increased expression of this degrading enzyme could shorten the availability of GABA, causing a disinhibitory effect. Increased ABAT expression could underlie manic symptoms in BP and SCHIZ, as ABAT deficiency has been associated with inconsolable crying, dullness, and lethargy (98) and increased ABAT expression has been associated with aggression in a preclinical model (99).…”
Section: Astrocyte-related Gene Expression In Bp and Schizmentioning
confidence: 99%
“…Increased ABAT expression could underlie manic symptoms in BP, as ABAT deficiency has been associated with inconsolable crying, dullness, and lethargy in case studies 107 and increased ABAT has been associated with aggression in rodents 108 .…”
Section: Astrocyte-related Gene Expression In Bp and Schizmentioning
confidence: 99%